Big Data; Data Mining; architecture; urban planning. - Diego Fiscarelli; Karina Cortina (Cuaderno Urbano, 2020)
This work retakes from everyday theories, the issues that constitutes urban planning as qualifier of the space in the city-housing interface, in order to identify parameters that contribute to a transdisciplinary assessment of Public Housing. It is hypothesized that there is an interdependent relationship between the scope of the Technical Standards for Housing Complex Projects (Institute of Housing of the Province of Buenos Aires, Argentina) and the strategies planning that are deployed to achieve adequate levels of urban-architectural quality. It is proposed as a case study a housing complex (La Plata) that, started in the 80s, undergoes local paradigm changes in Public Housing, and exposes transformations as a consequence of various policies and management modalities.